Child Development and His Efficient Education in Getting Pedagogical of the Process Main Principles and Approaches - Khakimovna, Mamatayeva Dilrabo (Researchparks Publishing, 2023)
In the article on child development and more efficient education to reach help giving pedagogical in process main principles and approaches discussion will be done and physical environment, social and cultural environment own into received comfortable education environment Create importance is displayed. Various young groups of children’s development features and of teachers’ study programs and lessons in making these features account get methods seeing will be released. He is also a child personality to form, including his intellectual, emotional, and social abilities to develop help giving main principles about what is spoken.